DETERMINATION OF MEANS OF CONTRAINDICATION OF OPERATIVE DAMAGE OF SUPERIOR WAGON-THERMAL SYSTEMS OF THE MODEL TN 4-201 (Transport systems and technologies, 2018)
The article presents the features and results of research work on the basis of the materials and documents provided, analysis of customer’s design features, a collegial survey of car damage, analysis of international experience in relevant research, formalized the nature of operational damage to load-bearing systems of freight cars using the thermos car model TN-4-201 construction of the plant "Dessau" Germany.Currently, in Ukraine and CIS countries, volumes of transportation of perishable foodstuffs for artificial, packaged and packaged goods have increased. Terms of transportation of these cargoes require the formation of a fleet of isothermal cars. For the creation and delivery of this type of carriages on the railways of Ukraine and other CIS countries, their development, production and testing are carried out.In this regard, it was proposed to carry out a research work on the definition of recommendations for counteracting operational damage to the load-bearing systems of freight cars on the example of the car-thermos model TN-4-201 construction of the Dessau plant in Germany. It is envisaged to work out concrete proposals for improving the load-bearing systems of freight cars.
Keywords: thermos car, carrier systems, welds, computer simulation, thermal insulation